(untitled) (Per Musi, 2015)
This article aims at making observations about the musician’s job market by assessing specific vectors, such as: which age they started music studying, their average salary and their formal instruction or lack of it. This is a quantitative research accomplished by means of data taken from a questionnaire, which was completed by 291 Brazilian musicians. Those issues may contribute to establish a projection of the benefit-cost ratio related to instruction and work in the area of Music.